Maslahat as Considerations of Islamic Law in View Imam Malik - Syarifuddin, Said (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
This study aims to reveal the view of Imam Malik about maslahat as an independent proposition in the determination of Islamic law. Trying to explain the terminology of maslahat, uncovering the dimensions of maslahat in the determination of Islamic law, analyzing maslahat as a basis of Islamic law that stands alone to establish Islamic law according to Imam Malik, and citing examples of Imam Malik's fatwa based on consideration of maslahat. This paper is a qualitative descriptive study using a multidisciplinary approach including normative, philosophical, and sociological approaches. This study shows that maslahat contains two sides, namely attracting or bringing benefit and rejecting or avoiding harm in order to maintain the goals of shari'ah, the establishment of Islamic law aims at realizing human benefit that is universal, generally accepted and lasting for all humans and in all circumstances. Imam Malik is of the view that maslahat can be used as a basis for independent legal considerations, without the need for legitimation of the shar'i proposition. For example, Imam Malik establishes the saliva of a holy dog. The fatwa is not in line with the instructions of the hadith that classify it as unclean. Imam Malik was not the first scholar to settle such a law, but his companions had experienced such cases, they then resolved these problems by issuing fatwas that were